Evaluasi Strategi Lot Sizing pada MRP untuk Optimasi Biaya Logistik Material Konstruksi - Simanjuntak, Martua; Mardiaman, Mardiaman (Jurnal Talenta Sipil, 2025)
Material Requirement Planning (MRP) is a critical approach for managing material procurement in construction projects to ensure timely delivery, avoid surplus inventory, and optimize logistical costs. In construction, inefficient planning often results in material shortages, excess stock, and delayed project completion, contributing to significant cost overruns. The choice of lot sizing strategy within the MRP system plays a central role in balancing ordering frequency and storage costs. While classical methods such as Economic Order Quantity (EOQ), and  Lot for Lot (LFL) are widely known, limited studies have applied a comparative evaluation of these methods specifically in construction logistics under real-world constraints. Most prior research emphasizes manufacturing applications, leaving a knowledge gap in dynamic, schedule-driven environments like public infrastructure projects. This study evaluates two lot sizing strategies, EOQ and LFL, using empirical data from a palm oil mill construction project in Mandailing Natal, Indonesia. A quantitative descriptive method was applied, utilizing data from master production schedules, bill of quantities (BOQ), and actual procurement cost records. The evaluation measured total procurement costs, ordering frequency, and inventory levels. The findings reveal that the LFL strategy results in the lowest total logistic cost at Rp 685,976,950.54, compared to EOQ at Rp 769,658,817.20, due to the complete elimination of holding costs despite higher ordering frequency. This implies that LFL is more suitable for government construction projects with short-term schedules and varying material demands, where minimizing storage risk is prioritized. The study contributes to procurement optimization under Indonesia’s public goods and services framework and recommends selective lot sizing strategies based on material characteristics and project dynamics.